2021
DOI: 10.1177/02676583211015803
|View full text |Cite
|
Sign up to set email alerts
|

Glottalization and linking in the L2 speech of Czech learners of Spanish, Italian and Portuguese

Abstract: The use of linking or glottalization contributes to the characteristic sound pattern of a language, and the use of one in place of the other may affect a speaker’s comprehensibility and fluency in certain contexts. In this study, native speakers of Czech, a language that is associated with a frequent use of glottalization in vowel-initial word onsets, are examined in the second language (L2) context of three Romance languages that predominantly employ linking between words (Spanish, Italian and Portuguese). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…This is perhaps because the use of creaky voice is often seen as an individual characteristic related to, for example, social status rather than as a feature of a language [39,40]. The few studies that have investigated creakiness in L2 focus on how well speakers can avoid creakiness in the target language [20,21]. Our results, however, suggest that using creaky voice in L2 Finnish can affect the perception of fluency and proficiency positively.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…This is perhaps because the use of creaky voice is often seen as an individual characteristic related to, for example, social status rather than as a feature of a language [39,40]. The few studies that have investigated creakiness in L2 focus on how well speakers can avoid creakiness in the target language [20,21]. Our results, however, suggest that using creaky voice in L2 Finnish can affect the perception of fluency and proficiency positively.…”
Section: Discussionmentioning
confidence: 62%
“…Language learners may thus be perceived as more native-like, if they manage to use creaky voice appropriately, while the absence of creaky voice can make the L2 speaker sound less fluent. However, studies on L2 and the use of creaky voice indicate that it is easier for a language learner to reduce creakiness than include it in speech [20,21], perhaps because creaky voice, in relation to modal voice, can be considered as an individual characteristic. Pillot-Loiseau et al [20] found that English learners of French -a language where creaky voice is considered unusual -reduced the use of creaky voice when speaking French compared to their L1 English, although they still used more creaky voice than native speakers of French.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another finding was the contribution of prosodic factors, including lexical stress (as in German) or the strength of the prosodic boundary (stronger boundaries tended to involve more glottalization). Many Romance languages -French, Spanish, Italian, Portuguese -behave similarly to English in this respect (Skákal, 2013;Di Napoli, 2015;Skarnitzl, Čermák, Šturm, Obstová & Hricsina, 2021). The main strategy in these languages is to link words smoothly without glottalization (thus por_otro, que_ahora and not por[ʔ]otro etc.…”
Section: Use Of Boundary Glottalization In Languagesmentioning
confidence: 99%